PREPARATION & EVALUATION OF HERBAL TOOTHPASTE - Saloni, Sethiya; Shailedra, Wadhwa (Asian Journal of Pharmaceutical Research and Development, 2016)
Dentifrices are the products which are used for oral hygiene such as freshness of mouth and to avoid tooth decay. The oral hygiene can be maintained throughout the day by using various dentifrices prepared by herbal and synthetic ingredients. In present study the toothpaste was prepared by using various herbal ingredients which possess antibacterial, antiseptic and cooling properties.